Chinese immigrants in the social, political, cultural and economic life of Canada - Болдуруковa Н. Б. (Journal of Oriental Studies, 2017)
Expands to Russia’s policy for the development of the Pacific coast, in particular of Sakhalin and the Kurile Islands. Showing the Russian expedition to the shores of the Pacific Ocean. Particular attention is paid to the expedition led by V.M. Golovnin, all the members of which were captured by the Japanese. Elucidate Russian first contacts with the Japanese, Russia’s attempts to establish diplomatic relations with Japan and the activities of I.D.Kasatkin (Nikolai’s father).